On Product‐based Accounts of Propositional Attitudes. (19th January 2015) - Felappi, Giulia
<x xml:space="preserve">Abstract</x> Propositional attitude sentences, such as <boxed-text content-type="quotation" id="tht3146-blkfxd-0001" position="anchor" orientation="portrait"> John believes that snow is white, </boxed-text> are traditionally taken to express the holding of a relation between a subject and what 'that'‐clauses like 'that snow is white' denote, i.e. propositions. On the traditional account, propositions are abstract, mind‐ and language‐independent entities. Recently, some have raised some serious worries for the traditional account and thought that we were mistaken about the kind of entities propositions are. Over the last ten years there has then been a boom of accounts of propositions in terms of (types of) mental acts (Burge 2007; Hanks 2011; Soames 2010). But Friederike Moltmann (2013; 2014) has recently suggested that in accounting for attitudes we should forget about mind‐ and language‐independent entities and (types of) acts and follow Twardowski (1912) in focusing instead on attitudinal objects, which are the products of our mental life. In this paper, I will focus on some semantic problems that any product‐based account seems to face. Moreover, I will show that product‐based accounts may be also criticised on ontological grounds. My conclusion will be that we lack a reason to think that in accounting for propositional attitudes we should focus on the alleged products of our mental lives.